The Influence of Pesantren Educational Background on Arabic Language Competence of Students in Islamic Higher Education - Azizah, Afida Khoirotul; Mukarromah, Fatihatul; Ainiy, Nurul (Institut Agama Islam Negeri Palangka Raya, 2023)
In the historical context of Arabic language development in Indonesia, the initiation of Arabic education took place in informal settings, notably in Islamic boarding schools (pondok pesantren). As time progressed, the prominence of Arabic language integration into formal education became more evident, spanning from elementary to tertiary levels. Arabic language learning involves four key language skills: listening (maharah istima’), speaking (maharah kalam), reading (maharah qiro’ah), and writing (maharah kitabah). Educationally, Arabic language proficiency is influenced by diverse factors, encompassing students' prior educational backgrounds. Field observations reveal that not all Arabic Education majors in Islamic higher education institutions originate from Islamic boarding schools, leading to variations in language competency levels. Consequently, this study focuses on assessing the impact of pesantren educational backgrounds on the Arabic language competence of students at IAI Sunan Kalijogo Malang, utilizing a qualitative descriptive research method. Findings indicate that students with pesantren backgrounds exhibit superior grammatical understanding of Arabic, while those without pesantren backgrounds excel in general linguistic and learning theories. However, both groups encounter challenges in mastering spoken Arabic (maharah kalam).